The Project Languages and Cultures at School: Presentation and Outcomes - Porsette, Igor; Alves da Paixão, Grace; Lanis, Cláudia; Kawachi, Cláudia (Guará Journal, 2019)
The aim of the project was raise learners' awareness to foreign languages, such as Spanish, French, English and Italian, and their respective cultures at Centro de Educação Infantil da Ufes (CEI - Criarte). It sought to promote a globalized, connected, multicultural and multilingual environment for the learners, focusing on linguistic and discursive development, as well as quality education, by raising young learners' awareness to linguistic, ethnic and cultural diversity. The activities were developed by Languages and Literature undergraduate students, followed by supervisors of each language. In addition, the Project aimed at filling the gap regarding the approach of children's language acquisition process and possibilities of teacher education for Languages and Literature (at Ufes) under graduate students – to contribute to their academic and professional development.
Keywords: Applied linguistics; Foreign language acquisition; Foreign language for children; Teacher education